2010
DOI: 10.1111/j.1469-7610.2010.02295.x
|View full text |Cite
|
Sign up to set email alerts
|

A population-based investigation of behavioural and emotional problems and maternal mental health: associations with autism spectrum disorder and intellectual disability

Abstract: ASD and ID are independent risk factors for behavioural and emotional problems. ASD (but not ID) is positively associated with maternal emotional disorder. Approaches to diagnosing hyperactivity and conduct problems in children with ASD may need to be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
267
5
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 350 publications
(291 citation statements)
references
References 48 publications
18
267
5
1
Order By: Relevance
“…For example, in a sample of 5 to 16-year olds with ASD and no intellectual disability, 74% had clinically significant emotional difficulties, such as anger, sadness or anxiety, compared to 18% of typically developing peers (Totsika, Hastings, Emerson, Lancaster, & Berridge, 2011). Approximately 40% to 50% of youth with ASD (as per DSM-IV-TR criteria) are estimated to meet criteria for two or more psychiatric disorders, often combining externalizing problems, such as ADHD, with internalizing problems, such as anxiety disorders (Leyfer et al, 2006;Simonoff, et al, 2008), leading many to conceptualize emotional problems as involving underlying difficulties with emotion regulation (Mazefsky et al, 2013;Mazefsky & White, 2014).…”
Section: Emotion Regulation Intervention In Asd 3 Brief Report Of Prementioning
confidence: 99%
“…For example, in a sample of 5 to 16-year olds with ASD and no intellectual disability, 74% had clinically significant emotional difficulties, such as anger, sadness or anxiety, compared to 18% of typically developing peers (Totsika, Hastings, Emerson, Lancaster, & Berridge, 2011). Approximately 40% to 50% of youth with ASD (as per DSM-IV-TR criteria) are estimated to meet criteria for two or more psychiatric disorders, often combining externalizing problems, such as ADHD, with internalizing problems, such as anxiety disorders (Leyfer et al, 2006;Simonoff, et al, 2008), leading many to conceptualize emotional problems as involving underlying difficulties with emotion regulation (Mazefsky et al, 2013;Mazefsky & White, 2014).…”
Section: Emotion Regulation Intervention In Asd 3 Brief Report Of Prementioning
confidence: 99%
“…For instance, in a population derived cohort of 5-to 16-year-olds, Totsika, Hastings, Emerson, Lancaster, and Berridge [2011] found that 85% of youth with ASD without an intellectual disability (ID) had clinically significant levels of hyperactivity, 74% of emotional problems, and 64% of conduct problems, compared to much lower rates in a typically developing comparison group (19% hyperactivity, 18% emotional problems, and 22% conduct problems). Further, youth with ID and ASD had higher rates of emotional disorders than those with only ID (88% vs. 63% for hyperactivity, 71% vs. 42% for emotional problems, and 65% vs. 46% for conduct problems, respectively).…”
mentioning
confidence: 99%
“…Parenting a child with autistic disorder has been associated with wide range of negative emotional outcomes [53]. Numerous studies have identified mental and physical health problems for parents of children with autism associated with high levels of stress [54]- [56].…”
Section: Parent Mental Healthmentioning
confidence: 99%